Interaction of vitamin D, homocystein and dental diseases - O.I. Kutelmakh (Zaporozhye State Medical University, 2019)
Over the past few years, the study of the influence of vitamin D and homocysteine (HC) on the metabolism and regulation of many important physiological processes in the life of the human body is particularly relevant. However, data on the influence of vitamin D and HC levels on the development of dental pathologies are limited. In this article, we discussed the main functions of vitamin D and homocysteine (НC) in the human body and their mechanisms and summarized the important reports on the effects of vitamin D and HC on the oral cavity. Conclusion. Vitamin D deficiency and hyperhomocysteinemia cause a significant amount of metabolic abnormalities in the body, which is a possible cause of a number of diseases of the oral cavity. Probably the effect of changes in the status of vitamin D on dental pathology is mainly due to a violation of phosphorous-calcium metabolism, including genetic origin, as well as inhibition of immune processes. Influence of hyperhomocysteinemia on the pathogenesis of oral cavity diseases can be related to the dysregulation of genetic processes, oxidative stress, osteoporosis, and endothelial dysfunction characteristic of this condition. In general, the importance of both factors - vitamin D deficiency and especially hyperhomocysteinemia in the pathology of individual organs of the oral cavity, nosological forms and related mechanisms - is insufficiently covered in the literature. There is no data on participation in the pathogenesis of dental diseases at the same time, both of these factors are absent at all. Thus, there is a need for further research in this direction with the use of modern biochemical, biophysical, morphological, molecularly-genetic and clinical-epidemiological studies, the implementation of which will contribute to the provision of dental human health.